Comparison of Readout-Segmented Echo-Planar Imaging and Single-Shot TSE DWI for Cholesteatoma Diagnostics - Wiesmueller, M.; Wuest, W.; May, M.S.; Ellmann, S.; Heiss, R.; Saake, M.; Janka, R.; Uder, M.; Laun, F.B. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The high diagnostic value of DWI for cholesteatoma diagnostics is undisputed. This study compares the diagnostic value of readout-segmented echo-planar DWI and single-shot TSE DWI for cholesteatoma diagnostics.MATERIALS AND METHODS: Thirty patients with newly suspected cholesteatoma were examined with a dedicated protocol, including readout-segmented echo-planar DWI and single-shot TSE DWI at 1.5T. Acquisition parameters of both diffusion-weighted sequences were as follows: b=1000 s/mm,2 axial and coronal section orientations, and section thickness of 3 mm. Image quality was evaluated by 2 readers on a 5-point Likert scale with respect to lesion conspicuity, the presence of susceptibility artifacts mimicking cholesteatomas, and overall subjective image quality. Sensitivity and specificity were calculated using histology results as the gold standard.RESULTS: Twenty-five cases of histologically confirmed cholesteatomas were included in the study group. Lesion conspicuity was higher and fewer artifacts were found when using TSE DWI (both P < .001). The overall subjective image quality, however, was better with readout-segmented DWI. For TSE DWI, the sensitivity for readers 1 and 2 was 92% (95% CI, 74%–99%) and 88% (95% CI, 69%–97%), respectively, while the specificity for both readers was 80% (95% CI, 28%–99%). For readout-segmented DWI, the sensitivity for readers 1 and 2 was 76% (95% CI, 55%–91%) and 68% (95% CI, 46%–85%), while the specificity for both readers was 60% (95% CI, 15%–95%).CONCLUSIONS: The use of TSE DWI is advisable for cholesteatoma diagnostics and preferable over readout-segmented DWI.rsDWIreadout-segmented echo-planar DWItseDWITSE DWI